Pengembangan Pariwisata Berbasis Kewirausahaan melalui Pemberdayaan Masyarakat Lokal di Pantai Tedunan, Seluma - Diki Ramadhani; M. Denny Kurnia Putra; M. Andi Abdulrozzaq; Jon Bon Jopi; Arum Puspitasari (Tamasya : Jurnal Pariwisata Indonesia, 2025)
Tedunan Beach in Seluma Regency, Bengkulu, holds exceptional potential as an ecotourism asset, attributed to its authentic and untouched natural landscape, featuring white sand stretches and a unique mangrove ecosystem. Sustainable tourism development, however, demands active participation and entrepreneurship from the local community, which is key to ensuring the equitable distribution of economic benefits and environmental preservation. This research aims to analyze the current community entrepreneurship models, identify challenges hindering business growth, and formulate strategic opportunities for development. Using a qualitative approach with a case study method, data was collected through in-depth interviews with business actors and community leaders, participant observation, and documentation studies. Findings indicate that community-based businesses have grown organically, albeit on a micro scale, encompassing fresh seafood culinary stalls, tourist hut rentals, and local guide services. Nevertheless, this growth is hampered by fundamental constraints: limited access to formal working capital, minimal promotion hindering market penetration, and a lack of professional training in financial management and tourism service standards. In response, an integrated development model is formulated recommending: increasing human resource capacity through business management and tourism awareness training, facilitating access to capital through partnerships, and strengthening digital-based promotion. In conclusion, Tedunan Beach tourism can be sustainable if supported by a comprehensive empowerment program that not only boosts economic income but also essentially fosters a sense of ownership and community responsibility towards the destination's preservation.